THE EFFECT OF THE SERVANT LEADERSHIP STYLE ON THE PERFORMANCE OF REGIONAL ORGANIZATIONS THROUGH THE CORE VALUES OF COMPETENT ASN AS AN INTERVENING VARIABLE - Fajar, Evi Triana Nurul; Thamrin, Mohammad; Supeni, Retno Endah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to analyze the effect of servant leadership style on the organization performance through the core value of competence as an intervening variable. Method: This research uses descriptive and quantitative research methods. The population to be studied is all staff of Regional Apparatus Organizations in Jember Regency, total 461 people. The number of samples used was 109 respondents and the sampling technique was nonprobability sampling with purposive sampling technique. Hypothesis testing in this research uses Structural Equation Modeling (SEM) with the WarpPLS statistical tool. Results: Findings of this research state that servant leadership style has a significant effect on the core value of competence and the organization performance. Core value of competence has significant effect on the organizational performance. The servant leadership style has a significant effect on employee performance through the core value of competence. Novelty: This research uses a model of the influence of servant leadership style on organization performance by involving the core value of competence as mediator or intervening. Thus, this model is the answer to the existing research gap related to organizational performance.